(untitled) (CIPEEX, 2025)
The Cerrado biome, recognized as the largest tropical savanna in the world, faces an alarming loss of biodiversity, driven mainly by the expansion of agricultural and livestock activities and the conversion of natural habitats into cropland. Between 2010 and 2020, about 6 million hectares of native vegetation were destroyed, resulting in local extinctions and significant population declines. This study aims to examine, through a literature review, the consequences of this degradation on the native herpetofauna of the Cerrado, compiling an inventory of species present in the state of Goiás and highlighting the importance of herpetofauna in natural communities. In addition to identifying the main threats—such as habitat fragmentation and climate change—this work proposes conservation measures, including continuous biodiversity monitoring, restoration of degraded habitats, and the promotion of environmental education. The sustainable management of agricultural activities is emphasized as a crucial strategy to balance agricultural production with biodiversity preservation. The study concludes that effective actions are necessary to mitigate anthropogenic impacts and ensure the sustainability of Cerrado ecosystems.